DIGITIZATION OF THE ECONOMY - REPORTING TO THE TOURISM INDUSTRY: THE GENERAL FRAMEWORK OF REGULATION, PROJECTIONS AND THE CURRENT SITUATION - Miruna Diana MOZA (Annals of the University of Oradea: Economic Science, 2021)
The way people carry out their daily activities has changed with digitalization. The digitalization process has highlighted its own effects on the economy as well as on society. Also, the way people travel has changed in terms of digitalization. Opportunities offered by this digitization process bring significant potential benefits. Thus, this paper proposes to make a brief foray and analyze the official documents that speak, plan and design the digital economy, which provides a set of projections of the digitalization of the economy, especially in the field of tourism. The analysis will be theoretical. In addition, this paper aims to give a brief overview of the current framework of the digital economy and to provide an analysis of the degree of involvement of public authorities at national level in the digitization of tourism in European countries and the number of online bookings in the same countries.